Gambaran Pengetahuan Gizi dan Kebiasaan Konsumsi Makanan Cepat Saji (Fast Food) pada Remaja di SMAN 10 Kota Jambi - Nadila, Nadila; Chandra, Filius; Hatussaadah, Siti Fati (3031-8572, 2024)
The Adolescents are an age group in transition from children to adults, experiencing a period of development and growth characterised by rapid psychological, cognitive and physical changes. Adolescents' nutritional knowledge can influence their food choices to meet their body's nutritional needs. In this modern era, there are many fast foods that are favoured by teenagers and supported by very attractive advertisements, so fast food is very fast in marketing, but the habit of consuming fast food can cause various health problems such as overweight. This study aims to determine the description of nutritional knowledge and consumption habits of fast food in adolescents at SMAN 10 Jambi City and was conducted in April-August 2024. This study is a quantitative descriptive study data collection by distributing nutrition knowledge questionnaires and FFQ questionnaires. The sample size was 85 adolescents. Data analysis in this study used univariate analysis to determine the description of nutritional knowledge and fast-food consumption habits. The results showed a picture of poor nutritional knowledge in as many as 44 respondents (51.8%), moderate in as many as 29 respondents (34.1%) and good in as many as 12 respondents (14.1%). The picture of fast-food consumption habits as many as 80 respondents (94.1%) do not usually consume and as many as 5 respondents (5.9%) usually consume. It can be concluded that there are still adolescents who do not understand nutritional knowledge and usually consume fast food. It is expected that the school must control the consumption of fast food among adolescents in school by educating the vendors in the school canteen, namely to sell snacks that are good and healthy for adolescents and to reduce the types of snacks and foods related to fast food.